Pandemic Covid 19: The Challenges of Online Learning Among UITMs' Students - Adida Muhammud; Najdah Abd Aziz; Rubiah Abu Bakar; Shahariah Harun (CSRC Publishing, Center for Sustainability Research and Consultancy Pakistan, 2022)
Purpose: In 2020, the emergence of Corona Virus Disease (COVID-19) has led Malaysia to an unprecedented public health crisis.  Due to this, all universities in Malaysia are forced to shut down any physical activities by the Government. Hence, Universiti Teknologi MARA (UiTM) had conducted an Online Distance Learning (ODL) starting on 13th April 2020 due to the spread of the Covid-19 virus. As a result, the government had to implement the Movement Control Order (MCO) to control the spread of the disease among the community. In attending online classes, a lot of challenges are faced by the students. Therefore, this study reveals out a few challenges:  time management, family support and financial crisis during online learning. Methodology: The sample of the study is 100 of UiTM students throughout Malaysia and the researchers set a form of questionnaires, distributed via google form to the respondents using convenience sampling. Findings: SPSS is used in analyzing the data and the result shows that all independent variables (time management, family support, financial crisis) are challenges towards online learning. Implications: Thus, this study will benefit the Ministry of Education, universities and students in managing and controlling their challenges while attending online classes during Pandemic Covid 19.